The Prognostic Value and Overexpression of Cyclin A Is Correlated with Gene Amplification of both Cyclin A and Cyclin E in Breast Cancer Patient - A. Husdal; G. Bukholm; I. R. K. Bukholm (Cellular Oncology)
Deregulation of cell cycle control is a hallmark of cancer. The primary cyclins (A, B1, D1, D3 and E) are crucial for cell cycle progression. Secondary cyclins (C and H) have putative indirect effects on cell cycle propulsion and are not previously evaluated in breast cancer. We have examined protein expression and gene amplification of cyclins in breast carcinomas and correlated the findings with clinical follow-up data. We have previously demonstrated that over-expression of cyclin A is associated with poor prognosis in breast cancer patients. In this study we wanted to evaluate the mechanisms behinde overexpression of cyclin A, as well as the impact of other cyclins, both at the gene level and at the protein level, on prognosis of breast cancer patients. The impact of TP53 gene mutations on gene amplification of cyclins was also evaluated. Methods: Real-Time Quantitative PCR was used to detect gene amplification of cyclins in tumour tissue from 86 patients operated for invasive breast carcinomas, while immunohistochemistry was applied to detect protein expression of the same cyclins. Result: Of the 80-breast tumour samples available for cyclin A gene amplification analyses, 26.7% (23/80) was defined to have cyclin A gene amplification. 37.2% (32/79) had cyclin B1 gene amplification, 82.6% (71/82) of the samples harboured amplification of cyclin C gene, 74.4% (64/82) had cyclin D1 gene amplification, 41.9% (36/86) had cyclin D3 gene amplification, 29.1% (25/81) of the patients had cyclin E gene amplification and 9.3% (8/86) of the samples showed amplification of the cyclin H gene. When correlation between gene amplification and protein expression was evaluated, we observed a statistical significant correlation between gene amplification and protein expression of cyclin A (p = 0.009) and cyclin D3 (p < 0.001). However, the correlation between gene amplification and protein expression of cyclin A, as well as the prognostic value of cyclin A overexpression, was affected by gene amplification of cyclin E. Gene amplification of none of the other cyclins was associated with patient prognosis. There was a statistical significant correlation between TP53 gene mutations and gene amplification of cyclins A, D3 and B1. No correlation was observed between gene amplification of secondary cyclins (H and C) and TP53 gene mutations. Conclusions: The overexpression of cyclin A is correlated to gene amplification of both cyclin A and cyclin E. Over-expression of cyclin A is associated with poor prognosis in breast cancer patients. When analysed in a multivariate analyses model, gene amplification as well as protein expression of none of the other cyclins than cyclin A are associated with patient prognosis in breast carcinomas. TP53 gene mutation seems to correlate with gene amplification of primary, but not secondary cyclins.